Do environmentally relevant concentrations of fluoxetine and citalopram impair stress-related behavior in zebrafish (Danio rerio) embryos? - Zindler, Florian; Stoll, Saskia; Baumann, Lisa; Knoll, Sarah; Huhn, Carolin; Braunbeck, Thomas (Chemosphere, 2020)
Selective serotonin reuptake inhibitors (SSRIs) have been shown to interfere with various physiological functions of aquatic organisms, yet the neuroactive potential of low concentrations of SSRIs in the aquatic environment is unclear. The current study investigated the effects of fluoxetine and citalopram on the visual motor response (VMR) of 107 h old zebrafish (Danio rerio) embryos. Results document a reduction in stress-related swimming activity of zebrafish embryos at environmentally relevant concentration levels, with fluoxetine being more effective than citalopram. Further experiments were designed to elucidate (1) if the lower neuroactive potential of citalopram is due to differences in uptake kinetics, (2) if the metabolite of fluoxetine, norfluoxetine, contributes to the neuroactive potential of fluoxetine, (3) and how SSRIs and their metabolites interact in equimolar mixtures. At the stage of 120 h, zebrafish embryos accumulate citalopram at significantly lower rates (up to 127 times) than fluoxetine. Moreover, it was demonstrated that norfluoxetine reduces the embryonic VMR similarly to fluoxetine resulting in additive effects of these substances on stress-related behavior in zebrafish embryos. In contrast, the interaction of fluoxetine, norfluoxetine and citalopram varied with test concentrations of the equimolar mixtures. Findings provide evidence that environmentally relevant concentrations of fluoxetine reduce stress-related behavior of zebrafish embryos, while these effects may be enhanced by the interaction of multiple SSRIs and their metabolites in environmental exposure scenarios.